LCD vs. E-ink: An Analysis of the Reading Behavior - Eva Siegenthaler; Laura Schmid; Michael Wyss; Pascal Wurtz (Bern Open Publishing, 2012)
Electronic books (e-book) are an interesting option compared to classic paper books. Most e-reading devices of the first generation were based on e-ink technology. With the appearance of the Apple iPad on the market, TFT-LCDs became important in the field of e-reading. Both technologies have advantages and disadvantages but the question remains whether one or the other technology is better for reading. In the present study we analyzed and compared reading behavior when reading on e-inkreader (e-ink displays) and on tablets (TFT-LCDs) as measured by eye-tracking. The results suggest that the reading behavior on tablets is indeed very similar to the reading behavior on e-ink-reader. Participants showed no difference in fixation duration. Significant differences in reading speed and in the proportion of regressive saccades suggest that tablets, under special artificial light conditions, may even provide better legibility.